Longitudinal effect of emotional and physical demands on health-related behaviour among Malaysian workers - Muhamad Nasharudin, Nurfazreen Aina (Human Resource Management Academic Research Society, 2021)
The current study examines the effect of job demands on psychological health-related behaviour among Malaysian workers. It is predicted that emotional and physical demands lead to future work-related burnout and depression and affect sleep patterns. This study was conducted among 345 Malaysian workers using a longitudinal two-wave survey. The data were analysed using AMOS software using Structural Equation Modelling (SEM). The results showed that emotional demands predict future work-related burnout, while depression predicts sleep problems through time. Overall, the current study shows that emotional and physical job demands affect employees’ psychological health over time.